Effects of future infrastructure development on threat status and occurrence of Amazonian birds - Vale, M. M.; Cohn-Haft, Mario; Bergen, Scott; Pimm, Stuart (Conservation Biology, 2008)
Researchers predict that new infrastructure development will sharply increase the rate and extent of deforestation in the Brazilian Amazon. There are no predictions, however, of which species it will affect. We used a spatially explicit model that predicts the location of deforestation in the Brazilian Amazon by 2020 on the basis of historical patterns of deforestation following infrastructure development. We overlaid the predicted deforested areas onto maps of bird ranges to estimate the amount of habitat loss within species ranges. We also estimated the amount of habitat loss within modified ecoregions, which were used as surrogates for areas of bird endemism. We then used the extent of occurrence criterion of the World Conservation Union to predict the future conservation status of birds in the Brazilian Amazon. At current rates of development, our results show that at least 16 species will qualify as threatened or will lose more than half of their forested habitat. We also identified several subspecies and isolated populations that would also qualify as threatened. Most of the taxa we identified are not currently listed as threatened, and the majority are associated with riverine habitats, which have been largely ignored in bird conservation in Amazonia. These habitats and the species they hold will be increasingly relevant to conservation as river courses are altered and hydroelectric dams are constructed in the Brazilian Amazon. © 2008 Society for Conservation Biology.
Keywords: Conservation Status; Dam; Deforestation; Ecological Modeling; Endangered Species; Endemism; Estimation Method; Future Prospect; Habitat Loss; Infrastructural Development; Prediction; Species Occurrence; Animals; Biological Model; Bird; Ecosystem; Electric Power Plant; Environmental Protection; Human Activities; Physiology; Population Dynamics; River; Tree; Animal; Birds; Conservation Of Natural Resources; Ecosystem; Human Activities; Models, Biological; Population Dynamics; Power Plants; Rivers; Trees; Amazonas; Amazonia; South America; Aves